Sentence Structure in Multiple Translations of Hemingway’s Novel "The Old Man and the Sea": A Contrastive Syntactic - Semantic Study - Al-Najjar, Fekry; Bahumaid, Showqi (Al-Adab Journal, 2025)
Within the framework of cultural cross-fertilization between nations, foreign literary works were translated into Arabic, Ernest Heminway’s (1953) The Old Man and the Sea was one of the most important translated novels. Over the years, multiple translations of this novel into Arabic were published. This study attempts to explore sentence structure and identify its specific features in the Arabic translations of that novel. It was prompted by the scarcity of syntactic studies on the various Arabic translations of this novel. The study further examines the impact of sentence structure and its semantic components on the quality of the Arabic translated texts. For the purposes of the study, renditions of ten randomly - selected texts from the English novel in three different modern Arabic translations of the novel were utilized. The study adopted both contrastive and analytical approaches for the investigation of the translated texts. The study findings revealed that while verbal sentences involving the past tense were used as the main narrative tool in the English text, their syntactic equivalents in the Arabic translated texts were dominated by the nominal sentence with the copied verb kaana (was). Besides, the Arabic lexical items used as equivalents to those in the English novel were characterized by clarity and precision with a relative variation among the three translations. A further finding is that the specific syntactic and semantic components of the Arabic sentences - in addition to the context - combined to make a positive impact on the quality of translation of those sentences. The study recommended expanding the scope of future research in the multiple translations of this novel to include the lexicon as well as both morphological and rhetorical aspects and activating censorship procedures on multiple translations of the same English novel by referring them to qualified and experienced reviewers to remove linguistic impurities before approving their publication.